2020
DOI: 10.1155/2020/1878917
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of MTHFR C677T Gene and the Associations with the Severity of Essential Hypertension in Northern Chinese Population

Abstract: Objective. Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of homocysteine metabolism and is closely related to the occurrence of hypertension. The aim of this study was to investigate the polymorphism of the (MTHFR) C677T and the factors influencing the severity of hypertension. Material and Methods. A total of 985 subjects were enrolled to analyze the polymorphisms of the MTHFR C677T gene by polymerase chain reaction (PCR). 306 people with essential hypertension were selected from 985 subjects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…There was no difference in the distribution of rs1801133 genotypes based on sex and ethnicity ( p value > 0.05), which was consistent with the report from the majority of previous studies [ 11 ]. However, we noted that patients in TT genotype were significantly younger than patients in CC or CT genotype group ( p value < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There was no difference in the distribution of rs1801133 genotypes based on sex and ethnicity ( p value > 0.05), which was consistent with the report from the majority of previous studies [ 11 ]. However, we noted that patients in TT genotype were significantly younger than patients in CC or CT genotype group ( p value < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Hcy is a sulfur-containing amino acid derived from the metabolism of methionine and is metabolized by one of the two pathways: remethylation or transsulfuration. Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of homocysteine metabolism, providing a methyl group for Hcy remethylation into methionine and maintaining the normal levels of Hcy in the body [ 11 ]. Mutations of the MTHFR gene decrease MTHFR enzyme activity that prevents Hcy remethylation and increases Hcy levels in plasma [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For his part, Karakantza et al, 31 in a study that included 15 women with PA, report high incidence of the MTHFR C677T mutation (40%), similar to Gebhardt et al, 32 which included 18 women with PA, found MTHFR C677T prevalence of 28%. In parallel, Song et al, 33 report in a group of 306 patients with hypertension MTHFR-C677T prevalence of 77.7%. In turn, Ya et al, 34 in systematic review, found prevalence of 2.6 to 47.06% of the MTHFR-C677T polymorphism in 8064 women with hypertension.…”
Section: Discussionmentioning
confidence: 88%